2020
DOI: 10.3390/jrfm13100238
|View full text |Cite
|
Sign up to set email alerts
|

Tools of Information and Communication Technologies in Ecological Marketing under Conditions of Sustainable Development in Industrial Regions (Through Examples of Poland and Ukraine)

Abstract: This scientific work analyzes the current state and problems of implementing the concept of sustainable development in industrial regions, in particular, in Poland and Ukraine. Emphasis is placed on slowing down the implementation of the main provisions of this doctrine, in particular, the violation of environmental requirements and non-compliance with ecological standards by industrial enterprises. The aim of the article is to find effective innovative tools for intensifying the process of implementing the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 23 publications
0
25
0
1
Order By: Relevance
“…[ 43 ] found that the modular design of suppliers affects the flexibility and agility of the supply chain. With the emergence of Industry 4.0 [ 44 ], 5G technology [ 45 ], the industrial internet of things [ 46 ], and new generations of other information technologies, the organizational change strategy based on intelligent empowerment represents the latest mode of advanced manufacturing development, such as the redistribution business [ 47 ], ecological marketing manufacturing [ 48 ], data-driven manufacturing [ 49 ], and customer service manufacturing [ 50 ] modes.…”
Section: Literature Reviewmentioning
confidence: 99%
“…[ 43 ] found that the modular design of suppliers affects the flexibility and agility of the supply chain. With the emergence of Industry 4.0 [ 44 ], 5G technology [ 45 ], the industrial internet of things [ 46 ], and new generations of other information technologies, the organizational change strategy based on intelligent empowerment represents the latest mode of advanced manufacturing development, such as the redistribution business [ 47 ], ecological marketing manufacturing [ 48 ], data-driven manufacturing [ 49 ], and customer service manufacturing [ 50 ] modes.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In addition, the factor-reflexive approach presented in the article can be integrated into already existing models of economic sustainability [3,[8][9][10]14,15,19,23,24,[59][60][61][62][63][64][65][66][67][68][69][70][71][72][73], and can also be used to form and adjust strategies of various scales and areas of management.…”
Section: Discussionmentioning
confidence: 99%
“…The energy security should be directly attributed to the areas of national security that ensure the realization of one of the fundamental national interests-sustainable development of the national economy, while ensuring other national interests-state sovereignty and independence [29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46].…”
Section: Methodsmentioning
confidence: 99%
“…The methodology is based on the concept of sustainable development from the standpoint of security [29] (pp. [41][42][43][44][45][46], which contains a general systematic perception of the ways of transition from the current position of the management object to the desired one and includes the following stages:…”
Section: Methodsmentioning
confidence: 99%